77‐1: Invited Paper: Ultra‐low Power OLED Microdisplay for Extended Battery Life in NTE Displays. Issue 1 (2nd June 2017) - Vogel, Uwe; Beyer, Beatrice; Schober, Matthias; Wartenberg, Philipp; Brenner, Stephan; Bunk, Gerd; Ulbricht, Steffen; König, Peter; Richter, Bernd
Abstract : Most of the current OLED microdisplays on the market have been designed for full‐video, i.e., high‐frame rate capability. However, specifically augmented‐reality (AR) near‐to‐eye (NTE) applications regularly demand long battery life above full‐frame rate. This is to report on a new backplane architecture combined with highly efficient OLED to achieve significantly reduced power consumption.